Autism spectrum disorder (ASD) and its perioperative management. Issue 11 (6th August 2015) - Taghizadeh, Neda; Davidson, Andrew; Williams, Katrina; Story, David; Thomas, Mark
Summary Autism spectrum disorder (ASD) is now diagnosed in more than 1 in 100 children, so it is not surprising that anesthetists are increasingly providing care for children with this diagnosis. The diagnostic classification for ASD has recently changed and our understanding of the causes and management of ASD are also changing rapidly. This review provides a timely update to increase understanding and awareness of the problems that children with ASD experience, and to minimize perioperative problems. Current literature on premedication and the increasing use of alpha‐2 agonists such as clonidine and dexmedetomidine as well as the use of old favorites midazolam and ketamine is reviewed. Some simple strategies that will improve care and decrease anxiety, like social stories, the use of tablet computers, other comfort items or games for distraction, and using favorite drinks to disguise the bitter taste of medications, are described. Remember, the parents are their child's expert and will know what agitates and settles them. Talking to them prior to the day of the procedure is ideal. The importance of staff training and having a clinical practice guideline available at every institution cannot be overstated.